Corrigendum to "Relationships between human activity and biodiversity in Europe at the national scale: Spatial density of human activity as a core driver of biodiversity erosion" [Ecol. Indicators 90 (2018) 356–365]. (April 2019) - Gosselin, Frédéric; Callois, Jean-Marc
Highlights: We studied statistically the human activity/biodiversity relationship in Europe. We corrected previous calculations of model comparison indices. We discuss the statistical rationale of the new results.